Analysing students’ perceptions of online mathematics learning / Nur Izza Hazwani Azali Azman and Zurina Kasim - Azali Azman, Nur Izza Hazwani; Kasim, Zurina (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Online distance learning is increasingly popular, particularly among students. Because students' learning abilities variety, it takes motivation and support from their surroundings to learn new things. Most students, especially non majors, consider mathematics to be one of the most difficult subjects. Because mathematics is such a broad topic, students must start with the basics. The purpose of this study is to analyze mathematics majors' learning using the fuzzy conjoint method. This chapter reviewed the sample size that will be used in this study, which will include as respondents Degree of Management Mathematics (CS248) final year students and Diploma in Mathematical Sciences (CS143) students from semester 4 and 5 of UiTM Perlis branch. The findings of this study will compare two levels of education: diploma and degree. As a result of analyzing the perception of online mathematics learning using the fuzzy conjoint method, the main objective of this study was achieved. Meanwhile, this study meets the specific objectives of comparing degree and diploma students' perceptions of online mathematics learning. According to the findings of this study, both diploma and degree students were rated neutral toward mathematics is hard to learn through online learning and the lecturers always give feedback on student assessment. However, students strongly disagreed that they are copying during the online tests and quizzes.